2019
DOI: 10.3390/app9081638
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Vaginal Hydrogels as a Multi-Drug Carrier for Contraception

Abstract: Injectable intravaginal hydrogels could deliver drugs systemically without hepatic first pass effect. This paper focuses on the contraceptive function of an injectable temperature-sensitive four-arm star-shaped poly(D,L-lactic-co-glycolic acid)-b-methoxy poly(ethylene glycol) (4sPLGA-mPEG) block copolymer hydrogels as a carrier of three drugs. In vitro controlled release profiles were investigated via HPLC, and it showed that the cumulative release amounts of indomethacin (IMC), gestodene (GSD), and ethinyl es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…ese three-dimensional hydrophilic polymer networks, held together either by chemical or physical interactions [9,10], absorb large amounts of aqueous fluids [11] coupled with a high permeability to small molecules and a soft consistency, which makes them similar to living tissues [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ese three-dimensional hydrophilic polymer networks, held together either by chemical or physical interactions [9,10], absorb large amounts of aqueous fluids [11] coupled with a high permeability to small molecules and a soft consistency, which makes them similar to living tissues [12].…”
Section: Introductionmentioning
confidence: 99%
“…eir applications encompass wound dressing uses [11], tissue engineering [13], and controlled drug delivery of a wide range of bioactive compounds [14], including antiviral drugs [10], contraceptives [12], and anticoagulants [15], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Reports have presented cases where it was used to characterize substances like benzotriazole [ 44 ], tetracycline [ 45 ], b-estradiol, estradiol benzoate, ethynyl estradiol etc. [ 46 ], as well as the extent to which binding was feasible.…”
Section: Methodsmentioning
confidence: 99%
“…With these established benefits of VDDS, and the many limitations/unwanted effects associated with current modes of hormonal contraceptive administration, safer and more patient-friendly intravaginal hormonal contraceptives—specifically, stimuli-responsive in situ hydrogels—are gaining attention and interest [ 78 , 181 ]. It has been demonstrated that formulations containing multiple drugs are more efficient contraceptives compared to single-drug formulations [ 122 , 181 ]. In this context, an in situ pH-responsive hydrogel containing indomethacin, gestodene, and ethinyl estradiol prevented pregnancy completely compared to a control group, which presented 100% pregnancy.…”
Section: Sol–gel Platform Technology In Vaginal Drug Delivery Systemmentioning
confidence: 99%